2006
DOI: 10.1002/app.25313
|View full text |Cite
|
Sign up to set email alerts
|

Silica nanoparticles modified with vinyltriethoxysilane and their copolymerization with N,N′‐bismaleimide‐4,4′‐diphenylmethane

Abstract: ABSTRACT:The synthesis and characterization of the vinyltriethoxysilane-modified silica nanoparticles were investigated. It was shown that the vinyltriethoxysilane molecules had been successfully grafted onto the silica nanoparticles. The native and silane-modified silica dispersions in N-methyl-2-pyrrolidone with the total solids contents within the range 1-6 wt % exhibited dramatically different flow behaviors. The polymerization of N,N 0 -bismaleimide-4,4 0 -diphenylmethane (BMI) initiated by barbituric aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…In an attempt to enhance the thermal stability of BMI/BTA polymers, vinyltriethoxysilane‐modified silica nanoparticles were prepared and characterized in our previous work . It was shown that the higher the level of silica, the better the thermal stability of the BMI/silane/silica composite particles.…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to enhance the thermal stability of BMI/BTA polymers, vinyltriethoxysilane‐modified silica nanoparticles were prepared and characterized in our previous work . It was shown that the higher the level of silica, the better the thermal stability of the BMI/silane/silica composite particles.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work using TGA was reported to calculate the content grafted onto the surface according to the difference in the weight loss between the native silica nano-particles and surface-modified silica nanoparticles [6,26]. But it cannot provide directly the knowledge about the nature of the adsorbed layers.…”
Section: Resultsmentioning
confidence: 99%
“…If suspension of filler in a fluid is exposed to an electric field, the electrostatic absorption force resulted from mutual dielectrophorisis of two adjacent particles is the main factor for creating a chain structure in the direction of electric field [6]. Some of the investigated surfactants not only stabilize the suspension by creating compatibility between organic polymer and inorganic filler, but also enhance the ER effect by increasing polarizability of the particles [7,8,9]. Application of a silane modifier in composites made of barium titanate dispersed in polyvinylidene fluoride showed a better dispersability of filler as well as improved mechanical and dielectric properties [8].…”
Section: Introductionmentioning
confidence: 98%